Implementative Strategy for Developing Moral and Social Responsibility Awareness of Muslim Scientists from the Perspective of Philosophy of Science - Riyan Nuryadin; Mohammad Sabarudin; Erni Haryanti (al-Afkar, Journal For Islamic Studies, 2026)
Muslim scholars play a central role in the development of knowledge that is beneficial and aligned with Islamic ethics, which emphasize moral and social responsibility in every scientific endeavor. However, awareness of these responsibilities still requires reinforcement so that scientific activities are not merely oriented toward academic achievement but also generate tangible social benefits. This study aims to identify implementable strategies for fostering moral and social responsibility among Muslim scholars from the perspective of the philosophy of science. The research employs a literature-based qualitative approach using critical descriptive analysis of key concepts in Islamic philosophy of science, scholarly ethics, character education, Islamic utilitarianism (maslahah), empathy, and Islamic hermeneutics. The main contribution of this study lies in the formulation of an integrative conceptual framework that connects Islamic philosophy of science with practical strategies for cultivating ethically responsible and socially committed Muslim scholars. The findings indicate that the integration of Islamic values, the strengthening of character education, and the development of empathy play a significant role in shaping scholars’ moral awareness and social responsibility. The implications of this study provide a conceptual and practical reference for Islamic educational institutions and scientific communities in developing an Islamic scientific culture oriented toward knowledge as an act of worship and as a means to enhance social welfare.